Transfusion ratios and survival in severe blunt trauma patients receiving massive transfusion - Toru Takiguchi; Tomohisa Seki; Takashi Tagami; Yu Akagi; Ryuta Nakae; Hiromasa Ito; Yoshimasa Kawazoe; Ichiro Okada; Shiei Kim; Masaaki Inoue; Kazuhiko Ohe; Shoji Yokobori (Scientific Reports)
Abstract The optimal transfusion ratios for severe blunt trauma requiring massive transfusion remain unclear. This nationwide retrospective cohort study used data from the Japan Trauma Data Bank (2019–2022) and included patients receiving ≥ 10 units of packed red blood cells (pRBC) within 24 h. The fresh frozen plasma (FFP)-to-pRBC and platelet concentrate (PC)-to-pRBC ratios were categorized as 0–0.5, 0.5–1, 1–1.5, 1.5–2, and > 2. Among 2,849 eligible patients, an FFP-to-pRBC ratio of 1–1.5 was associated with significantly higher in-hospital survival than 0.5–1 (adjusted odds ratio [OR], 1.46; 95% confidence interval [CI], 1.12–1.92; P = 0.006). A PC-to-pRBC ratio of 1.5–2 also showed a trend toward improved survival (1.62; 1.00–2.69; P = 0.053). Patients were categorized into three phenotypes: truncal trauma with shock (70.3%), moderate head and extremity trauma (11.8%), and severe head trauma with consciousness disturbances (17.9%). In the truncal trauma with shock phenotype, FFP-to-pRBC ratios of 1–1.5 (1.56; 1.12–2.20; P = 0.010) and > 2 (2.32; 1.14–5.10; P = 0.027) were associated with improved survival. Higher FFP-to-pRBC and PC-to-pRBC ratios may be associated with improved survival, especially in truncal trauma with shock.